2008
DOI: 10.1007/s11481-008-9137-z
|View full text |Cite
|
Sign up to set email alerts
|

TNF Alpha Production in Morphine-Treated Human Neural Cells Is NF-κB-Dependent

Abstract: The cytokine tumor necrosis factor alpha (TNFalpha) is a key factor in several inflammatory diseases and its levels increase in response to a variety of internal or external stimuli. The regulation of the TNFalpha promoter is mediated by several transcription factors including the nuclear factor kappa B protein (NF-kappaB). This study examines the role of NF-kappaB in the regulation of TNFalpha production by morphine in microglia. Using reverse transcriptase polymerase chain reaction, we demonstrated the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46). In our study, TNF-α levels in parents that consumed morphine were measured 3 months after withdrawal.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46). In our study, TNF-α levels in parents that consumed morphine were measured 3 months after withdrawal.…”
Section: Discussionmentioning
confidence: 85%
“…Chronic morphine exposure has also been shown to alter memory performance in rats, which has been associated with modification of TNF-α levels in the hippocampus (48). µ-Type opioid receptors are present in neural cells, and they increase the production of the transcription factor NF-KB through Mitogen-activated protein kinase (MAPK) intracellular pathways and transfer NF-KB into the nucleus (46,49). NF-KB binds to the TNF-α gene promoter and increases the expression of the TNF-α protein (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that, in cultured astrocytes from mice, exposure to morphine plus HIV Tat is sufficient to activate NF-κB and cytokine production [44] . Based on a number of previous studies showing that NF-κB regulates the expression of TNF-α, IL-1β, and IL-6 in immune cells and investigating the effects of TNF-α and IL-1β on NF-κB activation in glial cells [45] , it has been postulated that a positive feedback loop exists between pro-inflammatory cytokine expression and NF-κB activation [11] . Here, we found that chronic i.t.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 elevation after morphine (Johnston et al, 2004;Dave and Khalili, 2010) is dependent on sphingosine kinase (Muscoli et al, 2010), p38, CGRP , and TLR2 and could also be blocked by etanercept (Shen et al, 2011), naltrexone (Bokhari et al, 2009), amitriptyline (Tai et al, 2006;Tai et al, 2009), and propentofylline (Raghavendra et al, 2004a). Finally, morphine elevation of TNF-␣ (Johnston et al, 2004) is dependent on TLR2 , ceramide synthase ), p38, and CGRP ) and is sensitive to amitriptyline (Tai et al, 2006;Tai et al, 2009), naltrexone (Bokhari et al, 2009), naloxone, and ␤-funaltrexamine (Sawaya et al, 2009). Other nonclassic opioid ligands such as (ϩ)-morphine, (ϩ)-methadone and morphine-3-glucuronide are also capable of inducing upregulation of IL-1␤, IL-6, and TNF-␣ (Hutchinson et al, 2010a;Lewis et al, 2010), suggesting a possible role for nonclassic opioid pathways in inducing opioid proinflammatory responses.…”
Section: Opioid-induced Changes In Non-neuronal Cells Contribute To Tmentioning
confidence: 99%
“…The common downstream signaling consequence of these MAPK and related pathways is activation of NF-B. Morphine causes activation of NF-B within CNS non-neuronal cells in a fashion that depends on ceramide synthase , opioid receptor, p38, neuronal nitric oxide (Sawaya et al, 2009), calcium (El-Hage et al, 2008b, and CGRP .…”
Section: Initiation Of Non-neuronal Cell Intracellular Signaling In Tmentioning
confidence: 99%